2021
DOI: 10.20944/preprints202109.0418.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disposal Practices of Unused Medication Among Pharmacists in Libya

Abstract: Background and objective. Globally, disposing of unused medicines has become a source of concern, as pharmaceutical waste enters the ecosystem, posing a threat to human health and the environment. This study aimed to assess the disposal practice of unused medication among pharmacists in Libya. This study also seeks to determine if pharmacists plan to have their pharmacies serve as assembly points for potential take-back initiatives. Methods. A random sample of 150 pharmacists from various government and privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a similar study, in Nigeria, solid dosage forms were disposed of through the rubbish bin, drug distributors and NAFDAC (National Agency for Drug Administration and Control), while liquid dosage forms were disposed of in the sink (Michael et al, 2019). Improper disposal methods among community pharmacies have also been retorted in Libya and Iraq (Albaroodi, 2019; Atia, 2021). However, in Saudi Arabia, 70% of 360 pharmacies surveyed return unused expired medicines to the pharmaceutical distributor (Alghadeer and Al-Arifi, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, in Nigeria, solid dosage forms were disposed of through the rubbish bin, drug distributors and NAFDAC (National Agency for Drug Administration and Control), while liquid dosage forms were disposed of in the sink (Michael et al, 2019). Improper disposal methods among community pharmacies have also been retorted in Libya and Iraq (Albaroodi, 2019; Atia, 2021). However, in Saudi Arabia, 70% of 360 pharmacies surveyed return unused expired medicines to the pharmaceutical distributor (Alghadeer and Al-Arifi, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, 72.72% of participants were confirmed they were keeping it, while the other 25% discarding it. Similarly, an earlier study in Libya demonstrated that 53.1% of respondents said thatthrowing discarded drugs in thetrash bin was their preferred method of disposal [14] .…”
Section: Practicing Self-medicationmentioning
confidence: 85%
“… 3 , 4 A number of countries have implemented legislation pertaining to the appropriate disposal of unwanted or expired medicine. 5 Ensuring the effectiveness and safety of pharmaceutical items may be achieved by following the prescribed storage conditions specified on the label and using them prior to their designated expiry date. 6 , 7 The disposal of pharmaceuticals is often advised by suppliers and certain healthcare organizations, taking into consideration their expiry date.…”
Section: Introductionmentioning
confidence: 99%